2007
DOI: 10.5751/ace-00172-020208
|View full text |Cite
|
Sign up to set email alerts
|

Colony Dynamics and Persistence of Ivory Gull Breeding in Canada

Abstract: ABSTRACT. Despite the importance of assessing the viability of small and endangered populations, often few demographic data are available. However, when counts are available from discrete sites, a colony-or site-based approach can be useful. We used recent counts of Ivory Gull, Pagophila eburnea, a rare species that breeds at remote sites in the high Arctic, to model colony dynamics and population persistence. Colonization rates were low at 0.189 ± 0.054 (mean ± SE), new colonies were small (mean: 7.7 pairs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In fact, earlier studies have shown that for the ivory gull, the number of breeding adults reported from single censuses of a colony (e.g. all Greenland census presented in Table 1) is close to the total number of breeding pairs using the colony, hence advocating the use of a two-fold correction factor (Mallory et al 2008;Robertson et al 2007;H. Strøm, personal communication 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, earlier studies have shown that for the ivory gull, the number of breeding adults reported from single censuses of a colony (e.g. all Greenland census presented in Table 1) is close to the total number of breeding pairs using the colony, hence advocating the use of a two-fold correction factor (Mallory et al 2008;Robertson et al 2007;H. Strøm, personal communication 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The likely decline in southern colonies can be compared with recent trends reported for Canadian colonies (Gilchrist and Mallory 2005;Mallory et al 2003;Robertson et al 2007). In Canada, the 80% decline documented over a period of 20 years has been hypothesized to have resulted mainly from pollution and excessive hunting (e.g.…”
Section: Scenarios For Future Population Trends In Greenlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term monitoring of arctic vertebrate populations has been essential not only for developing policy and regulating harvest Peacock et al 2010;Higdon et al 2011), but also for input to international climate change analyses (Arctic Climate Impact Assessment ACIA 2005), regional land use planning and environmental assessment (Mallory and Fontaine 2004), and downlisting/uplisting species (Stirling and Parkinson 2006;Robertson et al 2007). Funding and logistical support during IPY made significant contributions to longterm time series for arctic vertebrates, including the standardization of metadata, establishment of long term archives and improving access to collected data.…”
Section: Discussionmentioning
confidence: 99%
“…The Seymour Island Migratory Bird Sanctuary in Nunavut (76.80˚ N,101.27˚ W) includes a small island supporting one of the largest remaining breeding colonies of ivory gulls known in Canada (Robertson et al, 2007). As part of a study to investigate the dispersal patterns and overwintering areas of ivory gulls, we flew to Seymour Island on 30 June 2010.…”
Section: Methodsmentioning
confidence: 99%